2024
DOI: 10.2147/cia.s434641
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment in the Emergency Department: A Prospective Cohort Study of Process, Clinical, and Patient-Reported Outcomes

Íde O'Shaughnessy,
Katie Robinson,
Aoife Whiston
et al.

Abstract: Background This study aimed to explore the process, clinical, and patient-reported outcomes of older adults who received an interdisciplinary Comprehensive Geriatric Assessment (CGA) in the emergency department (ED) over a six-month period after their initial ED attendance. Patients and Methods A prospective cohort study recruited older adults aged ≥65 years who presented to the ED of a university teaching hospital in Ireland. Baseline assessment data comprising a batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Regarding chronic kidney disease in the elderly, Chen et al [ 21 ] used CGA to comprehensively evaluate the levels of renal function, cognition, emotional state, nutritional status, and social support in different stages of the disease and guided patients’ health care. O'Shaughnessy et al [ 22 ] reported that CGA in the emergency department could lead to improved outcomes by reducing the negative impacts of potentially preventable hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding chronic kidney disease in the elderly, Chen et al [ 21 ] used CGA to comprehensively evaluate the levels of renal function, cognition, emotional state, nutritional status, and social support in different stages of the disease and guided patients’ health care. O'Shaughnessy et al [ 22 ] reported that CGA in the emergency department could lead to improved outcomes by reducing the negative impacts of potentially preventable hospital admissions.…”
Section: Discussionmentioning
confidence: 99%